Jordan's National Security Under King Hussein - Abu Shariah, Hamzeh Ismail Ibrahim (2000)
This study examines Jordan's national security during King Hussein's reign. The late King focused on security and stability issues, and this thesis analyzes the factors that affected the enhancing of his country's national security. The most important of these factors were his personality, military institutions, the role of the tribes, national covenant, the Palestinian question, the Jordan-Israeli peace treaty, and Jordan's relations with the oil producing Arab states. In addition to the presentation of Jordan's history, this study analyses its national historical experience, historical environment, and its political experience in order to understand how it managed to overcome the political obstacles and threats faced by its national security.This study follows the descriptive approach and analytical method for the thoughts and given concepts in Jordan's national security and moreover, it discusses all the factors and elements that affect the kingdom's national security. Jordan's political system has bridged major difficulties in the building of its social stability and the preservation of its national security. The elimination of the factors affecting its national security is solely attributed to the late king's ability and wisdom. Jordan managed to enter into the international political arena despite the limitation in its resources and abilities. The condition of its security and stability, which makes Jordan distinctive, is rare. This is what attracted the world's concern, in particular the United States. It is known that Jordan faced successive historical challenges because of its geographical location, borders, and the conditions of its surrounding environment, in addition to pressure of domination on the part of the great powers.